2012
DOI: 10.1038/eye.2011.366
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcome in Japanese patients with Acanthamoeba keratitis

Abstract: Purpose To identify prognostic factors affecting visual outcome in Acanthamoeba keratitis (AK) treated with topical chlorhexidine gluconate (CHG). Methods A total of 35 eyes in 34 patients with AK were treated with 0.02% topical CHG. Patients were divided into two groups according to the final visual outcome: Group 1, final visual acuity (VA) of 20/25 or greater (22 eyes); Group 2, less than 20/25 (13 eyes). We compared these groups and evaluated the effectiveness of topical CHG compared with outcomes in previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…However, five cases (14.7%) were identified in our series as DDCL users. This is similar Yamazoe  et al ’s study14 where seven out of 34 cases (20.5%) were DDCL users. We agree with his statement that it is difficult to generalise the level of risk of AK in DDCL users as CL care and practices differ greatly among individuals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, five cases (14.7%) were identified in our series as DDCL users. This is similar Yamazoe  et al ’s study14 where seven out of 34 cases (20.5%) were DDCL users. We agree with his statement that it is difficult to generalise the level of risk of AK in DDCL users as CL care and practices differ greatly among individuals.…”
Section: Discussionsupporting
confidence: 88%
“…The low average incidence of 2 per year in our study is similar to studies where an outbreak has not been reported, both in Australia11 12 and in other countries such as New Zealand,7 Hong Kong,9 Japan14 and USA (Cleveland4 and Philadelphia3), where the number of cases has ranged from 1.5 per year to 3.6 cases per year. Melbourne’s clean water could account for the low incidence of AK; Melbourne has some of the highest quality drinking water in the world where great care is taken to disinfect water sources via chlorination, chloramination and ultraviolet irradiation 15.…”
Section: Discussionsupporting
confidence: 88%
“…In some centres, epithelial debridement is performed at diagnosis . This is thought to remove some of the organism load and aid penetration of the anti‐amoebic drugs to deeper layers of the cornea.…”
Section: Course and Managementmentioning
confidence: 99%
“…58 In some centres, epithelial debridement is performed at diagnosis. 59 This is thought to remove some of the organism load and aid penetration of the anti-amoebic drugs to deeper layers of the cornea. It appeared effective in small case series, 59 however to fully assess this practice, a randomised controlled trial would be needed.…”
Section: Course and Managementmentioning
confidence: 99%
“…Other documented causes include swimming and showering with contact lenses in situ , exposure to contaminated water or soil, and corneal trauma. Some studies showed that AK was more prevalent during warmer seasons, especially during the summer,[ 63 64 65 66 ] but others revealed no significant seasonal differences. [ 67 ] This difference is perhaps due to more swimming and showering in summer.…”
Section: Resultsmentioning
confidence: 99%